Miniaturized printed YAGI‐Uda antenna with high directivity for long range UHF RFID item tracking systems. Issue 2 (February 2017) - Kim, J.‐H.; Jeong, M.‐G.; Bae, S.‐H.; Lee, W.‐S.
ABSTRACT: A miniaturized printed Yagi‐Uda antenna with high directivity for long‐range ultra‐high‐frequency radio frequency identification item tracking systems is presented. The proposed antenna consists of a meandered driven element and a reflector to obtain a compact size and high directivity. Using a printed microstrip balun, the proposed antenna is fed by a 50‐Ω microstrip line in a printed circuit board. The peak gain and maximum front‐to‐back ratio of the proposed antenna are ∼4.5 dBi and 17 dB at the authorized UHF RFID band in Korea, respectively. The antenna physical size is 80 × 45.5 mm 2 (approximately 0.25 λ 0 × 0.14 λ 0 at 920 MHz). © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:439–441, 2017